Building power through reindigenization: Sharing the story of Menīkānaehkem. Issue 8 (11th November 2021) - Faust, Victoria; Pollard, Ethen; Welch, Kristin; Hilgendorf, Amy; (Anahkwet) Reiter, Guy; Brown, Tony; Thunder, Cherie; Wescott, Sara; Wilber, Dawn; Christens, Brian D.; Wells, Alexandra
Abstract: Culture shapes and animates how community organizing is understood and carried out in specific contexts. Many frameworks for examining organizing, however, do not effectively attend to the influences of culture. Greater understanding of how culture can be imbued in organizing can help to ground it in the social realities of organizing participants and can advance approaches to organizing that honor the past and present of specific cultures. This study details local culturally grounded community organizing work rooted in Indigenous, and specifically Menominee, culture. First, it provides a description of the formation of the organization Menīkānaehkem in the Menominee Nation and includes examples of how current organizing practices of Menīkānaehkem build from long‐standing Menominee cultural practices. It then highlights the reinvigoration of cultural practices, or re‐indigenization, as an important goal for community power building in Menīkānaehkem. It ends with a discussion of the importance of culture in frameworks for understanding, analyzing, and promoting organizing as an endeavor to advance well‐being in a way that also interrupts cycles of structural oppression, such as legacies of settler colonialism.